ANALYSIS OF FACTORS AFFECTING THE QUALITY OF BPK RI AUDIT REPRESENTATIVE OF THE RIAU ISLANDS - Nisfu Ramadhani; Dian Efriyenti (Jurnal Ekonomi, 2023)
In Indonesia, questions about audit quality often arise in connection with cases where the name of the auditor is not clearly stated. In line with the findings of the BPK audit on the loss of liquidity assistance banks, Otto Hasibuan and Sjamsul Nurasalim in Indonesia. He continued to say that the BPK was not independent in this case. Lantara conducted an investigation according to the KPK's request that they admit the incident in question. The purpose of this study is to understand how the level of expertise, reliability, and integrity of auditors relate to quality inspection at the BPK Representative office of the Riau Islands. The majority of respondents in this survey were around 40 auditors who worked at the BPK Representative Office for the Riau Islands. The technique used in Sample Sampling is Statistical Sampling using a small sample size, around 40 respondents. The primary data used, and the methods of analysis include descriptive statistics, classical hypotheses, and multiple-linear regulatory analysis used to support the previous hypothesis. The current study confirms the notion that the variable integrity has a statistically significant effect on the quality of audits at the BPK Representative Office of the Riau Islands. However, statistically there is no significant correlation between auditor work experience and accountability status at the BPK Kepri Representative Office. However, when combined, the many variables of auditor skills, integrity and honesty make a significant difference in audit quality at the BPK Representative Office of the Riau Islands. The results of the analysis show that simple variables can influence complex dependent variables by 44.6%, and independent variables can also reveal other independent variables by 55.4% outside the scope of this study.